PENDIDIKAN AGAMA KRISTEN DALAM KELUARGAPERAN LITERASI DIGITAL ALKITABIAH DALAM MEMBENTUK KARAKTER ANAK PADA KELUARGA MASA KINI - Ferida Liunokas; Maria Tanopo; Taroci Tse; Werner Adif Loban; Yosina Sipa (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
In a rapidly evolving world, accompanied by rapid technological advancements, children are confronted with a massive flow of information. This presents a significant challenge and requires special attention from today's Christian parents in their parenting styles, which shape the character of their children. This study explores the importance of biblical digital literacy, a tool for Christian parents to guide their children, especially in the ever-evolving digital world, guided by the Holy Spirit. Biblical digital literacy is defined as the ability to filter and evaluate digital content based on biblical values. The method used is descriptive qualitative, employing a literature study approach. The analysis utilizes digital ethics, family theology, and child developmental psychology to formulate simple work procedures for today's Christian families. The results demonstrate that biblical digital literacy plays a crucial role in Christian families, serving as a platform for building integrity, self-discipline, and spiritual critical thinking. As Christian parents, we must be wise in controlling and integrating technology use, both in communication and digital literacy, amidst the changing times. The conclusion of this study states that biblical digital literacy is an important foundation for building children's character to remain ethical and have integrity in the Christian faith amidst the dynamics of the ever-changing era.